One nose, one brain: contribution of the main and accessory olfactory system to chemosensation - Mucignat, Carla; Redaelli, Marco; Caretta, Antonio (Frontiers in Neuroanatomy, 2012)
The accessory olfactory system is present in most tetrapods. It is involved in the perception of chemical stimuli, being implicated also in the detection of pheromone. However, it is sensitive also to some common odorant molecules, which have no clear implication in intraspecific chemical communication. The accessory olfactory system may complement the main olfactory system, and may contribute different perceptual features to the construction of a unitary representation, which merges the different chemosensory qualities. Crosstalk between the main and accessory olfactory systems occurs at different levels of central processing, in brain areas where the inputs from the two systems converge. Interestingly, centrifugal projections from more caudal brain areas are deeply involved in modulating both main and accessory sensory processing. A high degree of interaction between the two systems may be conceived, and partial overlapping appears to occur in many functions. Therefore, the central chemosensory projections merge inputs from different organs to obtain a complex chemosensory picture.